DEVELOPMENT OF PROBLEM-BASED LEARNING SCIENCE E-MODULE INTEGRATED WITH ETHNOSCIENCE OF PENCAK SILAT TO IMPROVE STUDENTS' SCIENCE PROCESS SKILLS - Junartiah Junartiah; Sri Retno Dwi Ariani; Umi Fatmawati (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
The integration of local culture into science learning has become increasingly important to enhance contextual understanding, foster student engagement, and strengthen the relevance of scientific concepts in daily life. However, many learning resources still lack meaningful connections between scientific material and students’ cultural backgrounds, which may limit their motivation and science process skill development. To address this gap, this study aims to develop and evaluate a science e-module based on the Problem-Based Learning (PBL) model integrated with pencak silat ethnoscience, focusing on the topic of the human respiratory system.to develop a Problem-Based Learning (PBL) e-module integrated with ethnoscience pencak silat to improve students' science process skills in respiratory system material. The development model employed a 4-D model (Define, Design, Develop, Disseminate). The e-module was developed based on the needs analysis results, designed according to the structure and format of digital learning media, and validated by material, media, learning, and language experts. The instrument's validity was analyzed using Aiken's V, with results ranging from 0.84 to 0.91, indicating high validity. The product was tested through limited and medium-scale trials, involving 2–3 teachers and 6–24 students, which resulted in positive responses with average percentages above 87%. The effectiveness test through pretest and posttest in experimental and control classes across three schools showed significant improvements in the experimental class. Data analysis using independent sample t-tests indicated significant differences in posttest scores (p < 0.05). The developed e-module proved to be effective, practical, and valid in enhancing students' science process skills, Integrating scientific concepts with local cultural wisdom through pencak silat not only enriches students’ contextual understanding of science but also fosters cultural appreciation, strengthens identity, and promotes the relevance of science learning to real-life experiences.